P0498CLINICAL PRESENTATION AND RENAL HISTOPATHOLOGICAL FINDINGS IN PATIENTS WITH MONOCLONAL GAMMOPATHY. (6th June 2020) - Alfano, Gaetano; Delrio, Alice; Fontana, Francesco; Ferrari, Annachiara; Solazzo, Andrea; Mori, Giacomo; Cappelli, Gianni
Abstract: Background and Aims: Monoclonal gammopathy is associated with renal lesions due to the toxic effect of M-protein. The aim of our study was to evaluate the prevalence and the clinical presentation of monoclonal gammopathy in patients who underwent kidney biopsy for renal impairment. Method: We conducted a retrospective study at the Nephrology and Dialysis Unit of the University Hospital of Modena from 2005 to 2017. The diagnosis of renal disease was proved histologically. Results: Monoclonal gammopathy was found in 179 out of 1334 patients (13.4%). Mean age was 66.1±13.4 years with a predominance of males (63.7%). There was no differences (P=0.16) between the age of patients with benign (64.9±14.3) and malignant lymphoproliferative diseases (67.6±12). The hematologic disorders involved in the production of M-protein were MGUS (51.9%), myeloma multiple (MM) (25.7%), amyloidosis (8.9%) smoldering MM (5 %), non-Hodgkin lymphoma (NHL) (6.7%) and HL (1.7%). The prevalence of MGUS was estimated to be 6.97% (93/1334). Mean serum creatinine was 2.68±2.12 mg/dl (eGFR of 35.24±29.32 ml/min) and urine protein/creatinine ratio of 5.1±6.5. None of the study subjects progressed to MM or other lymphoproliferative diseases. The most common kidney disease was membranoproliferative (GN) (19.3%). MGRS has been identified in five patients (5.4%). Mean age of MM was 66.84±13 years. Serum concentration M-protein was 1.47±0.98. Among patients with AKI (89.1%), 13 patients (28.2%) required urgent hemodialysis. Histological evaluation showed cast nephropathy (71.7%), MM-associated AL amyloidosis (15.2%), MM-associated-light chain deposition disease (4.3%) and interstitial nephritis (8.7%). Nine patients had a diagnosis of smoldering MM . Average age was 69.17±10.8 years old. At presentation, creatinine was 2.31±2.6 mg/dl (GFR of 41.35 ml/min). Evaluation of renal biopsies allowed us to identify different patterns of glomerular diseases, expression of an aspecific renal involvement of this hematological disease. AL amyloidosis was secondary to MGUS (75%) and smoldering MM (33%). Mean age was 66.04±11.7 years old. At presentation mean urine protein/creatinine ratio was 8.33±3.2 concomitant to a serum albumin level of 2.74±0.84 gr/dl. Mean creatinine was 1.4 mg/dl corresponding to eGFR= 56.5 ml/min. Average age of NHL patients was 72.6±9.6 years. Renal function was extremely variable at presentation; mean creatinine was 2.4±1.6 mg/dl (eGFR of 30.4±22.7 ml/min). Histological evaluation of biopsy specimen revealed amyloidosis (25%), cryoglobulinemic GN (25%), LCDD (16.6%), cast-nephropathy (8.3%), LCDD (8.3%) and other renal diseases (16.8%). Three patients (1.12%) had a diagnosis of HL at mean age of 69.04±5.3 years. At presentation, renal function was normal in all patients with a creatinine of 0.93±0.07mg/dl (eGFR of 62.7.3±7.4 ml/min). Urine protein/creatinine ratio was 0.3±0.2. Kidney biopsy revealed cryoglobulinemic GN (75%) and hypertensive nephrosclerosis (25%). ANOVA analysis did not found statistically significant differences in age (p=0.11) and serum concentration of M-protein (P=0.42) between groups. The differences in mean serum creatinine and mean urine protein/creatinine ratio were statistically significant between groups, (P<0.0001) and (P=0.003), respectively. A post hoc Tukey test showed that proteinuria was higher in AL amyloidosis compared to MM and HL, whereas renal function was worse in MM patients compared to the others. Conclusion: MGUS was the most common monoclonal gammopathy. Surprisingly, it is frequently associated with membranoproliferative glomerulonephritis. MGRS is a rare histopathological entity (5.4%). MM manifests frequently with AKI whereas AL amyloidosis with nephrotic syndrome. Renal function was extremely variable in NHL patients; on the other hand, the limited number of HL patients with renal involvement in our cohort does not allow generalization of our findings.